Intercropped Bt and non-Bt corn with ruzigrass (Urochloa ruziziensis) as a tool to resistance management of Spodoptera frugiperda (JE Smith, 1797) (Lepidoptera: Noctuidae) - Jacques, Filipe L; Degrande, Paulo E; Gauer, Evandro; Malaquias, José B [UNESP]; Scoton, Ana Maria N (Wiley, 2021)
BACKGROUND: Corn intercropped with ruzigrass is common in Brazil, and it can improve the physicochemical features of soils, increase water retention, and suppress the emergence of resistant weeds and soil nematodes. As both corn and ruzigrass are hosts to Spodoptera frugiperda (the main corn pest in South America), the cultivation of both these plants in the same place at one time motivates investigation into the pest population dynamics. We hypothesize that the intercropping system influences S. frugiperda pressure and leaf injury in corn. Considering that if corn hybrids with high dose toxin expression are used, ruzigrass may be a potential host to susceptible S. frugiperda larvae, consequently an alternative refuge and be included as a tool for the resistant management of Bt corn. To test these hypotheses about the use of ruzigrass as an alternative host of S. frugiperda in an intercropping system with corn, we conducted field trials in three seasons to verify S. frugiperda population dynamics and leaf injury to crop systems. In addition to phenotypic evaluation, we also characterized molecularly S. frugiperda strains collected in corn and ruzigrass to identify strain differences. RESULTS: The insects collected in both corn and ruzigrass were identified as corn strains. Ruzigrass was used as a S. frugiperda host during all crop cycles. The intercropped system did not increase the S. frugiperda population or leaf injury on Bt corn. CONCLUSION: The results suggest that the intercropped system is not prejudicial to Bt corn cultivation since high dose concept applies to all larvae instars. The results also suggest that ruzigrass may be used as a promising alternative refuge in Bt corn agroecosystems, if compliance with management strategies is followed.
Keywords: alternative host; Brachiaria ruziziensis; fall armyworm; resistance; Santa Fé system; Vip3Aa20